Phosphorus deficiency tolerance in sorghum - Sopandie, Didy; Trikoesoemaningtyas; Desta Wirnas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Sorghum is a globally important commodity for food, feed, and fuel, and is known to have a high tolerance to heat, drought, and other abiotic stresses, and have a large genetic variation for grain yield under low-P conditions. Agricultural land in Indonesia is dominated by acid soils with limited P availability, of a total of 144.5 million ha, around 107.3 million ha are acid soils. Information regarding the tolerance of sorghum to P deficiency conditions is still very limited. The review aimed to discuss the adaptation strategy of sorghum to P deficiency. Studies showed that sorghum has a moderate adaptation to Al3+ stress with low P. Under various P levels, the performance of sorghum was also very diverse following the wide genetic diversity. From evaluations of several varieties and inbred lines with high tolerance to P deficiency that has been obtained, sorghum tolerance strategies to low P conditions are: (1) increase root size (length, diameter, and volume), and root proteoid on several genotypes, (2) increase secretion of oxalic acid, particularly in tolerant genotypes, the secretion of which are higher when Al3+ is present, (3) higher P-use efficiency (PUE), eventhough the specific absorption ratio (SAR) was lower than the sensitive ones. The high PUE is thought to contribute to higher grain weight compared to sensitive genotypes under P starvation condition, and (4) higher stay green percentage, which has a high correlation to grain weight/plant. Such strategies should be considered in precission breeding program of sorghum to P deficiency. Keywords: adaptation strategy; oxalic acid; P-use efficiency; sorghum genotypes; sorghum low P; stay green